The Effectiveness of Mexico’s Faculty Improvement Program (Promep) in Public State Universities - Guzman, Teresa; Martínez-Arcos, Cruz Alberto (Education Policy Analysis Archives, 2015)
This article evaluates the effectiveness of Promep, a faculty improvement program implemented by Mexico’s Federal Department of Public Education (SEP) since 1996 to improve the academic qualifications, performance, and organization of faculty at the public higher education institutions. This evaluation examines the degree to which Promep has achieved its quantitative objectives with regard to the Public State Universities (PSU), which is the higher education subsystem that Promep has been active in for the longest period of time (1996–2013). The evaluation is based on numerous data reports published by Promep, the SEP, and other federal institutions as well as on essential subsystem-wide indicators calculated from data individually collected from each of the PSU for the purposes of this study. The results indicate that Promep has significantly improved the academic qualifications, performance, and organization of the full-time faculty staff of the PSU, but also that by 2013 the program has not been able to meet the quantitative goals it expected to achieve by late 2008, which was its initial deadline. The study suggests that the failure to achieve these initial and manageable goals has occurred mostly because many PSU have allowed the infringement of their own faculty recruitment, permanence, and promotion regulations and Promep has failed to stop these practices through the establishment of more drastic strategies, such as binding agreements and penalization schemes.